2009
DOI: 10.1007/s10802-009-9312-6
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Problems in ADHD: Degree of Association, Shared Endophenotypes, and Formation of Distinct Subtypes. Implications for a Future DSM

Abstract: We aimed to assess which comorbid problems (oppositional defiant behaviors, anxiety, autistic traits, motor coordination problems, and reading problems) were most associated with Attention-Deficit/Hyperactivity Disorder (ADHD); to determine whether these comorbid problems shared executive and motor problems on an endophenotype level with ADHD; and to determine whether executive functioning (EF)-and motor-endophenotypes supported the hypothesis that ADHD with comorbid problems is a qualitatively different pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
79
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 48 publications
12
79
1
3
Order By: Relevance
“…The results of this study showed that the motor performance of GII students was superior than the performance of GI students, in almost all motor areas assessed; which supports the literature (Rochelle & Talcott, 2006;Rommelse et al, 2009;Capellini, Germano, & Padula, 2010;Rosenblum, Aloni, & Josman, 2010;.…”
Section: Discussionsupporting
confidence: 87%
“…The results of this study showed that the motor performance of GII students was superior than the performance of GI students, in almost all motor areas assessed; which supports the literature (Rochelle & Talcott, 2006;Rommelse et al, 2009;Capellini, Germano, & Padula, 2010;Rosenblum, Aloni, & Josman, 2010;.…”
Section: Discussionsupporting
confidence: 87%
“…It will be worthwhile to examine MAOB and evaluate the gene-gene interaction between MAOA and MAOB in further research given the important role of MAOB in the metabolism of DA. In recent years, endophenotypes have attracted attention in genetic studies of ADHD [Doyle et al, 2005a;Doyle et al, 2005b;Rommelse et al, 2008b;Rommelse et al, 2008c;Rommelse et al, 2009;Uebel et al, 2010]. Increased penetrance of the endophenotype compared to the phenotype proper may help us to find candidate genes.…”
Section: Discussionmentioning
confidence: 99%
“…It has proven useful in populations other than ASD such as ADHD for characterizing subthreshold ASD problems (Nijmeijer et al 2008) and delinquent groups ('t Hart-Kerkhoffs, Jansen, Doreleijers, Vermeiren, Minderaa, Geluk et al 2012). The validity of the CSBQ also follows from genetic (Nijmeijer et al 2010), neurocognitive (Blijd-Hoogewys, van Geert, Serra, andGeurts, Luman, and van Meel 2008;Rommelse et al 2009) and behavioral (de Bildt et al 2005;Jaspers et al 2013) studies.…”
Section: Instrumentsmentioning
confidence: 99%